Antibiotic prescription rate for upper respiratory tract infections in general practice – a Croatian study - Anja Gačina; Marija Vrca Botica; Iva Botica; Andrea Horvat Hodžić; Iva Borovečki Žuti; Antonio Kobaš (Medicinski glasnik, 2019)
Aim: Acute upper respiratory tract infections are the most common indication for antibiotic prescribing in primary care. The frequency of antibiotics prescribed to patients with upper respiratory tract infections has been studied. Methods: A cross-sectional survey has been conducted from October to December 2017 with participation of 17 General Practices in Croatia. Visits of patients with symptoms of upper respiratory tract infections made the survey framework. A specially structured questionnaire was a tool for the assessment of reasons for encounters, clinical statuses and practitioners' decisions. According to the registered clinical status, two independent doctors classified patients using Centor criteria, which were used to evaluate appropriate indication for antibiotic prescription. Results: The survey analysed 709 patients' visits. Seventy three percent of general practice visits due to acute respiratory tract infection were initial. Antibiotics had been prescribed in the total of 32.6% of cases. Analysing upper respiratory tract infections with Centor score 1 and 2, antibiotics had been prescribed in 22.8% cases of the first visit and in 31.7% of the second visit, and with the Centor score 3 and 4 antibiotics had been prescribed in 85.1% of cases during the initial visit, and 66.7% of cases during the second visit. Logistic regression analysis about the contribution of nonclinical variables to antibiotic prescribing showed that most often antibiotics had been prescribed on Mondays. The most prescribed group of antibiotics was the penicillin group (74.8%), followed by macrolides (17.6%) and cephalosporins (4.0%). Conclusion: General practitioners prescribe antibiotics for acute respiratory tract infections more than recommended by evidence based medicine and professional criteria.
Keywords: antibiotic prescribing; Centor criteria; primary care